Masyarakat dan Pendidikan: Tinjauan tentang Eksistensi Masyarakat sebagai Lingkungan Pendidikan - Ristianah, Niken (Kartika: Jurnal Studi Keislaman, 2021)
In the educational process there is an environment that caneffect the educational process. The environment is a family environment (informal), the school environment (formal), and the community environment (non formal), where there environment is a place or place for someone to get an education either directly or indirectly. The three educational environments are between one environment and another, meaning that the three environments have various duties and functions of each. Education in the community is a vehicle for the application of interaction and implementation of various knowledge gained as well as a mirror of learning outcomes implied in self-actualization. In society, children will be able to imitate and practice in everyday life from what has been obtained in family and school directly educational institutions organized by the community are one element of implementing the principle of life long education, meaning that education provided in the family environment (informal) and the shool environment (formal) has limitations, it is in the community tht people will continue their education until the end of his life. All things related to the knowledge and skills acquired the family education environment and in the school environment will be able to develop and be develoved and can be felt the benefits in the community.